Connectivity and Functionality of the Globus Pallidus Externa Under Normal Conditions and Parkinson's Disease - Dong, Jie; Hawes, Sarah; Wu, Junbing; Le, Weidong; Cai, Huaibin (Frontiers in Neural Circuits, 2021)
The globus pallidus externa (GPe) functions as a central hub in the basal ganglia for processing motor and non-motor information through the creation of complex connections with the other basal ganglia nuclei and brain regions. Recently, with the adoption of sophisticated genetic tools, substantial advances have been made in understanding the distinct molecular, anatomical, electrophysiological, and functional properties of GPe neurons and non-neuronal cells. Impairments in dopamine transmission in the basal ganglia contribute to Parkinson’s disease (PD), the most common movement disorder that severely affects the patients’ life quality. Altered GPe neuron activity and synaptic connections have also been found in both PD patients and pre-clinical models. In this review, we will summarize the main findings on the composition, connectivity and functionality of different GPe cell populations and the potential GPe-related mechanisms of PD symptoms to better understand the cell type and circuit-specific roles of GPe in both normal and PD conditions.